2022
DOI: 10.3390/vaccines10020264
|View full text |Cite
|
Sign up to set email alerts
|

Metrics from Wearable Devices as Candidate Predictors of Antibody Response Following Vaccination against COVID-19: Data from the Second TemPredict Study

Abstract: There is significant variability in neutralizing antibody responses (which correlate with immune protection) after COVID-19 vaccination, but only limited information is available about predictors of these responses. We investigated whether device-generated summaries of physiological metrics collected by a wearable device correlated with post-vaccination levels of antibodies to the SARS-CoV-2 receptor-binding domain (RBD), the target of neutralizing antibodies generated by existing COVID-19 vaccines. One thousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…While the absolute changes are small and would be unrecognizable in a standard healthcare setting, these findings, and their consistency with reported subjective reactogenicity, highlight the value of wearable sensors to detect subtle deviations from an individual’s “normal.” With knowledge of an individual’s pre-vaccine “normal” 22 26 , we were able to identify changes in RHR of at least one standard deviation above an individual’s usual, pre-vaccine RHR pattern in ~half of individuals following their second vaccine dose. As there are currently no non-invasive, objective means of detecting a response to vaccines in a scalable manner, these findings, along with other recent work 17 , provide a potential novel mechanism to identify individuals with either a suboptimal or exaggerated immune response to a vaccine.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…While the absolute changes are small and would be unrecognizable in a standard healthcare setting, these findings, and their consistency with reported subjective reactogenicity, highlight the value of wearable sensors to detect subtle deviations from an individual’s “normal.” With knowledge of an individual’s pre-vaccine “normal” 22 26 , we were able to identify changes in RHR of at least one standard deviation above an individual’s usual, pre-vaccine RHR pattern in ~half of individuals following their second vaccine dose. As there are currently no non-invasive, objective means of detecting a response to vaccines in a scalable manner, these findings, along with other recent work 17 , provide a potential novel mechanism to identify individuals with either a suboptimal or exaggerated immune response to a vaccine.…”
Section: Discussionmentioning
confidence: 87%
“…The relationship between reactogenicity symptoms after vaccination and immune response is controversial 15 , although one study of a COVID-19 vaccine identified a direct correlation between the duration of time between a first and second vaccine dose, reactogenicity and eventual humoral immune response 16 . In addition, a recent study found a significant relationship between individual changes in physiologic parameters measured using a smart ring and ~30 day antibody levels 17 .…”
Section: Introductionmentioning
confidence: 98%
“…Early proof-of-concept data from the DETECT 6 study and from other studies 7 9 confirm that consumer wearable sensors can detect the individual physiological and behavioral changes associated with the vaccination and the consequent inflammation. All three studies 7 9 identified significant post-vaccine changes in daily summary values of physiological and behavioral parameters relative to their pre-vaccine individual baselines. The level of deviation from normal was moderate.…”
mentioning
confidence: 82%
“…The potential value in identifying these small, individual changes was demonstrated by Mason et al 9 in their study of over 1,000 individuals with wearable data from a smart ring and with post-vaccination SARS-CoV-2 receptor-binding domain antibody levels. They identified a significant and direct correlation between the change in several physiological parameters and immunogenicity, with the strongest independent predictor being temperature deviation.…”
mentioning
confidence: 99%
“…Alternate solutions are also in development, such as wearable sensors capable of correlating vaccine-induced physiological changes to antibody and cell-mediated responses ( 47 ), Interferon release assays ( 48 ), TCR sequencing systems ( 49 ), and skin tests ( 50 ). Innovations link these could greatly reduce the cost and complication of evaluating the cell-mediated immune response, rendering these assessments more accessible for clinical trials.…”
mentioning
confidence: 99%